RELATIONSHIP BETWEEN KNOWLEDGE AND ATTITUDE WITH SEX BEHAVIOR OF TEENANGER AT SMKN 1 BENGKULU - Hanifah hanifah hanifah; Ade Herman Surya Direja; Jesshinta Ramayani (Universitas Bengkulu, 2020)
Free sex behavior is a sexual activity that carried out without being based on a legal marriage relationship. Among adolescents the behavior occurs because most of them do not know the impact of free sex behavior. In addition, free sex behavior can also damage their future. This study aimed to determine the relationship between knowledge, attitudes, and sexual behavior among adolescent in SMKN 1 Bengkulu City. A quantitative study with cross sectional design was conducted in 80 respondents, who were selected using simple random sampling. Most of the respondents had good level of knowledge (78.8%), had most favorable attitudes (81.2%) and had most low risk sexual behavior (90.0%). The data were analyzed by using Fisher's Exact test, and obtained p-value = 0.001. It is showed that, there is relationship between knowledge and sexual behavior, with moderate category. There is relationship between attitude and sex behavior with p-value = 0,000 with a close category. It is recommended that SMKN 1 through counseling teachers to provide health education about sexual behavior and its effects so as to prevent free sex behavior among adolescents.